Nominal GDP targeting and the zero lower bound: Should we abandon inflation targeting? - Roberto M. Billi (Sveriges Riksbank, 2013)
I compare nominal GDP level targeting to flexible inflation targeting in a small New Keynesian model subject to the zero lower bound on nominal policy rates. First, I study the performance of optimal discretionary policies. I find that, for a standard calibration, inflation targeting under discretion leaves the economy open to a deflationary trap. Nominal GDP level targeting under discretion, by contrast, provides a firm nominal anchor to the economy. Second, I study simple policy rules and the role of smoothing in the rules. With smoothing, a Taylor-type rule performs as well as a nominal GDP level rule. These result suggest that inflation targeting should not be ditched. Still, it can be improved significantly, by using policy rate smoothing to anchor inflation firmly.
Keywords: E31; E52; E58; 330; nominal GDP target; optimal policy; simple rules; zero lower bound